Evaluating desirable characteristics of PHD supervisors in an open distance learning context. - Chu, Shuk Lee; Siow, Heng Loke (International Association of Technology, Education & Development, 2010)
An experienced research supervisor plays an important role in providing support to supervise students and thus, the student-supervisor relationship also plays a vital part in order to work together to achieve desirable results in PhD graduates. This relationship has always been fundamental to PhD research, yet received little attention in the literature especially in an open distance learning (ODL) context. The main purpose of this paper is to evaluate desirable characteristics of PhD supervisors as well as investigate any significant patterns emerging from interactions between student and supervisor in an ODL setting. Both quantitative, but predominantly qualitative methods of data collection and analysis were employed. Quantitative data were collected using adapted forms of established supervisory instruments. Qualitative data were collected via in-depth, semi-structured face-to-face interviews. The participants were selected from PhD student-supervisor matched-pairs or dyads at three stages of the research processes in an ODL context. The study found that supervisory relationship, supervisory styles, student autonomy and power issues were interrelated and linked to the success of students completing their PhD programme. In the case of an ODL situation, remote supervision and students’ perceptions that students were given too much freedom by their supervisors were seen as factors in failures. Taking cognizance of these findings (namely, that students wanted more structured and detailed guidance and feedback from their supervisors) a quality assurance framework for effective supervision in the ODL context is proposed.